Students’ Satisfaction, Attitude and Behavioural outcome in Higher Educational institutions (With specific reference to Management Programme) - Kalpana, M (Journal of Contemporary Research in Management (JCRM), 2017)
This research focuses on the students’ expectation, overall satisfaction, attitude and their behavioural outcome towards four categories of educational institutions (Standalone, Technical, Arts and Science and Universities) offering management programme in Coimbatore. The primary objective is to study the gap existing if any between expected and perceived institution’s quality among four categories of educational institutions offering management programme and to study the impact of institution’s quality factors, emotions, cognitive dissonance, students’ overall satisfaction, and attitude on behavioural outcome. The descriptive method of research was adopted for this study. Primary data was collected using a structured questionnaire. The study was carried out among management graduates belonging to four categories of institutions namely Standalone, Technical, Arts and Science, and Universities offering management programme in the city of Coimbatore. Proportionate stratified random sampling technique was used to identify the respondents. The sample frame consists of 3580 students from four categories of 49 institutions. The sample size for the study comprises of 608 respondents as (142 in 3 Standalone, 214 in Technical, 170 in Arts and Science and 82 from Universities. Statistical tools like percentage analysis, t-test, correlation, multiple regression,discriminant analysis, path analysis using VPLS, and ANOVA were used for analysis. This study had found that respondents belonging to Standalone and Technical institutions were satisfied with the institution’s quality factors, whereas there exist significant difference between the means scores of expectation and perception towards institution’s quality factors among the respondents of Arts and Science institutions and Universities. It is also found that institution’s quality factors have major impact on overall satisfaction of students followed by emotions whereas cognitive dissonance was found to have negative relationship with overall satisfaction of the students. Further, it was found that students attitude towards the institution had high impact on behavioural outcome when compared to overall satisfaction of the respondents.It can be found that there was significant difference among the demographic factors gender, age, family monthly income, institution category and behavioural outcome. The two important aspects of the study were likely to be of special interest to policy makers of higher educational institutions. First, it confirmed that positiveperception of institution’s quality could result in positive word of mouth and recommendation of institution to others. Second, overall satisfaction and attitude were found to be the antecedents to behavioural outcome of students. This study suggests that educational institution assessment by stakeholders starts with perception of the quality of service offered by the institutions. The priorities of policy makers were at the transaction level of institution’s quality and take efforts to improve the institution’s quality attributes. All the institution’s quality factors were under the control of the educational administrators except attitude and behavioural outcome. Thus, at the transactional level, institution’s quality was considered to be the most important for education administrators. It becomes imperative that higher education policy makers and administrators should monitor students’ perception of institution’s quality and satisfaction. Clear understanding of students’ perception of quality and satisfaction will enable the administrators to serve them better and provide a quality experience. This will, in turn, result in improving the image, reputation and financial performance of higher educational institutions and their profitability. This study will help the service providers to design a quality improvement strategy for their institutions to improve their quality of service as perceived by the students’ and thus will provide guidelines for the strategic planning of their institutions